La innovación en el Turismo Comunitario como alternativa de desarrollo local en la parroquia rural Santiago de Calpi, cantón Riobamba - Astrid Vanessa, Amaguaña Arredondo (2022)
RESUME The objective of this research work is to design innovation strategies for community tourism from the context of local development of the rural parish of Santiago de Calpi, Riobamba canton, fundamentally the community tourism centers were characterized and the ventures focused on community tourism were identified. with potential for tourism innovation. The applied research method is deductive and inductive, the quantitative methodology was applied, through this research problems that directly affect community tourism development were identified. The type of research used is documentary, descriptive, explanatory, correlational and field. The research design is non-experimental because the data was collected in an established period from a total of 164 respondents from the Royal Palace, La Moya, Jatari Campesino and Quilla Pacari. The results obtained were processed in the IBM SPSS 22 program, where the great interest they have in developing community tourism innovation in their territory could be denoted. The reliability of the instrument corresponding to the independent variable (innovation), and the dependent variables (community tourism and local development) was demonstrated by means of Cronbach's Alpha, concluding that the instrument has an acceptance and reliability criterion as Good. At the same time, the hypothesis verification was carried out with the Chi-square method where the alternative hypothesis (H1) is accepted and the null hypothesis (H₀) is rejected. Finally, a marketing plan was designed that leads to the innovation of community tourism in the rural parish of Santiago de Calpi, which aims to design plans to promote community tourism in the parish, for which the mission, vision and objectives were raised. medium and long-term goals; Two strategies were proposed related to the dissemination of the natural and cultural attractions of the Santiago de Calpi Parish through social networks and the development of advertising material for the development of community tourism. KEY WORD: innovation, community tourism, local development, marketing plan